(untitled) (European Journal of Economics, Finance and Business Development, 2024)
According to the decree of the Cabinet of Ministers of the Republic of Uzbekistan dated 09.11.2020 No. 699, the implementation of the procedure for calculating and maintaining the rating of Project - Search and construction-contracting organizations is established. This decision included the procedure for the formation and maintenance of rating data of legal entities registered on the territory of the Republic and whose main activity consisted in the implementation of construction and installation work and services, as well as the corresponding license for the development of urban planning documents.